57‐4: Invited Paper: Progress on Key Innovations in Direct‐View μLED Display Manufacturing. Issue 1 (28th June 2022) - Zhu, Mingwei; Ng, Hou T; Ganapathiappan, Sivapackia; Li, Zhiyong; Visser, Robert; Patibandla, Nag
Abstract : Applied Materials reported earlier on an innovative approach to μLED‐based front plane technology using a single wavelength GaN LED emitter with Cd‐free quantum dots for color conversion. This proprietary μLED front plane technology incorporates several key innovations such as the use of high external quantum efficiency dice in ultraviolet wavelength spectrum (vs. red/green/blue), highest photon extraction efficiency at small die‐size, fewer number of mass transfer steps with high yield, and a four‐subpixel backplane architecture to allow for a simple, cost‐effective repair strategy. A picture of this display is shown below.